(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Due to the day to day innovations and development in construction field, the use of natural aggregates is increased tremendously and at the same time, the production of solid wastes from the demolitions of constructions is also quite high. Because of these reasons the reuse of demolished constructional wastes like ceramic tile and granite powder came into the picture to reduce the solid waste and to reduce the scarcity of natural aggregates for making concrete. The ceramic tile waste is not only occurring from the demolition of structures but also from the manufacturing unit. The investigation finds out with the partially replacement of fine aggregate with ceramic waste and steel fiber with coarse aggregate in the concrete mix of M30 was made and fresh and hardness test were examined after 7 and 28 days. The investigation was achieved on cement concrete in which partially replacement of fine aggregate at percentage of 0%, 5%, 10%, 15% and 20% with ceramic waste and steel fiber with coarse aggregate at a percentage of 0%, 10%, 20% and 30% in M30 grade of concrete respectively.